CircNRIP1 Exerts Oncogenic Functions in Papillary Thyroid Carcinoma by Sponging miR-653-5p and Regulating PBX3 Expression. (19th May 2022) - Fu, Lijun; Huo, Jia; Fitrat, Habibullah; Kong, Yujing; Zhang, Lingyu; Shang, Chaoyang; Li, Guoquan; Ji, Feihong; Fu, Xinghao; Qiu, Xinguang
Abstract : Background . Circular RNA circ_0004771 (termed circNRIP1) was identified by RNA-Seq previously and was elevated in papillary thyroid carcinoma (PTC) tissues. A series of studies also showed that circNRIP1 was upregulated in some tumors and could promote the malignant progression of tumors. This research intended to focus on the role of circNRIP1 in PTC progression and explore the mechanisms underlying circNRIP1 functions. Methods . RT-PCR or western blot determined circNRIP1, miR-653-5p, and pre-B-cell leukemia homeobox 3 (PBX3) expression. EdU, CCK-8, Tunel, and transwell assays determined cell proliferation, apoptosis, invasion, and migration, respectively. Luciferase reporter assay, RNA immunoprecipitation (RIP), and RNA pull down assays clarified the target relation between miR-653-5p and circNRIP1 or PBX3. Xenograft models were applied to explore the role of circNRIP1 in vivo . Results . circNRIP1 significantly increased in PTC tissues and PTC cell lines than that in normal ones. Higher circNRIP1 expression was associated with the TNM stage and poorer overall survival. circNRIP1 knockdown attenuated the malignant progression of PTC, specifically by inhibiting proliferation and invasion/migration and promoting apoptosis. circNRIP1 was a miR-653-5p sponge; miR-653-5p knockdown reversed the suppressive role of circNRIP1 silence in PTC progression. PBX3, a target of miR-653-5p, was positively medicated through circNRIP1 via competitively sponging miR-653-5p. Knockdown of circNRIP1 attenuated the PTC tumor progression via miR-653-5p/PBX3 axis. Conclusion . Silencing of circNRIP1 suppressed PTC development via miR-653-5p elevation and PBX3 reduction, providing a novel perspective for understanding PTC pathogenesis.